2022
DOI: 10.1155/2022/3601942
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Patients’ Baseline Characteristics and Survival Benefits in Immunotherapy-Treated Non-Small-Cell Lung Cancer: A Systematic Review and Meta-Analysis

Abstract: Background. The difference of patients’ baseline characteristics such as sex, age, Eastern Cooperative Oncology Group performance status (ECOG PS), and smoking status may influence the immune response. However, little is known about whether these factors affect the efficacy of immune checkpoint inhibitors (ICIs) in patients with advanced non-small-cell lung cancer (NSCLC). Therefore, we performed this systematic review and meta-analysis to investigate the relationship between patients’ baseline characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…A seminal meta-analysis of advanced NSCLC randomized controlled trials of PD-(L)1 inhibitors showed that compared to chemotherapy alone, chemoimmunotherapy benefits females more than males whereas ICI monotherapy benefits males more than females 27 . Subsequent meta-analyses could not replicate these findings, reporting no sex difference in response to either treatment group, but may have introduced heterogeneity by including CTLA-4 inhibitor, non-first line therapy and adjuvant trials 30 , 32 . Of note, these studies had no access to patient level data and could not directly compare males to females.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A seminal meta-analysis of advanced NSCLC randomized controlled trials of PD-(L)1 inhibitors showed that compared to chemotherapy alone, chemoimmunotherapy benefits females more than males whereas ICI monotherapy benefits males more than females 27 . Subsequent meta-analyses could not replicate these findings, reporting no sex difference in response to either treatment group, but may have introduced heterogeneity by including CTLA-4 inhibitor, non-first line therapy and adjuvant trials 30 , 32 . Of note, these studies had no access to patient level data and could not directly compare males to females.…”
Section: Discussionmentioning
confidence: 99%
“…Better identification of patients likely to benefit from immunotherapy is clearly needed. Recent studies report conflicting findings on the influence of sex and BMI on response to ICIs 5 11 , 25 30 , 32 34 , while emerging evidence suggests a potential link between cachexia status and poor response to ICIs 12 15 , 18 . In this retrospective study, we evaluated the effects of sex, BMI and PWL on outcomes in metastatic NSCLC patients treated with ICIs as part of standard of care at our institution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been some evidence from several randomised trials suggesting that immunotherapy was much more efficacious in men than in women [29,30], although other studies did not demonstrate the same distinction [31]. In our small patient cohort, we did not find any gender-specific survival benefit post-immunotherapy treatment, but did observe a trend for men to more likely to experience irAEs, and when they did, their irAEs appeared to be of higher severities than that in women.…”
Section: Discussionmentioning
confidence: 99%